2014
DOI: 10.2106/jbjs.m.00330
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Alignment and Integrity of the Sustentaculum Tali in Intra-Articular Calcaneal Fractures

Abstract: Prognostic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…We defined the sustentaculum tali as the portion of the calcaneus extending 13 mm from the most medial prominence and evaluated it on axial, sagittal, and coronal CT images ( Figure 2). 16,20 Sustentacular displacement was defined as fragment translation more than 2 mm in any plane. 16 All operations were performed after swelling diminished, which was confirmed by positive wrinkle sign.…”
Section: Preoperative Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…We defined the sustentaculum tali as the portion of the calcaneus extending 13 mm from the most medial prominence and evaluated it on axial, sagittal, and coronal CT images ( Figure 2). 16,20 Sustentacular displacement was defined as fragment translation more than 2 mm in any plane. 16 All operations were performed after swelling diminished, which was confirmed by positive wrinkle sign.…”
Section: Preoperative Managementmentioning
confidence: 99%
“…16,20 Sustentacular displacement was defined as fragment translation more than 2 mm in any plane. 16 All operations were performed after swelling diminished, which was confirmed by positive wrinkle sign.…”
Section: Preoperative Managementmentioning
confidence: 99%
“…Berberian et al in 2013 [ 46 ] retrospectively reviewed the computed tomography (CT) scans of 88 patients with 100 DIACFs for evidence of sustentacular displacement and found that the fragment was displaced in 40% of fractures. Gitajin et al in 2014 [ 47 ] reported similar results in 20 % of DIACFs. However currently, there is no data to evaluate a combined medial and lateral approach and its effect on the functional outcome.…”
Section: The Myth Of the “Constant Fragment”mentioning
confidence: 77%
“…Therefore, special attention should be paid to the integrity and alignment of the sustentacular fragment prior to surgical fixation. 102…”
Section: Displaced Sustentacular Fragmentmentioning
confidence: 99%